(untitled) (Universal International Scientific Journal, 2026)
This article highlights the modern didactic content of developing coaching competence in future specialists. The results of research on the development of coaching competence, which is currently required in masters studying pedagogy and psychology, pedagogy, are highlighted. The module “Personal Psychology and Coaching” taught in this direction is taught in 2 courses, 3-4 semesters. Statistical data before and after the course of this module were compared in the experimental and control groups based on six criteria, and the results are presented.